Identifying key knowledge needs for evidence‐based conservation of wild insect pollinators: a collaborative cross‐sectoral exercise. Issue 3 (12th October 2012) - Dicks, Lynn V.; Abrahams, Andrew; Atkinson, John; Biesmeijer, Jacobus; Bourn, Nigel; Brown, Chris; Brown, Mark J.F.; Carvell, Claire; Connolly, Chris; Cresswell, James E.; Croft, Pat; Darvill, Ben; et al.
Abstract: In response to evidence of insect pollinator declines, organisations in many sectors, including the food and farming industry, are investing in pollinator conservation. They are keen to ensure that their efforts use the best available science. We convened a group of 32 'conservation practitioners' with an active interest in pollinators and 16 insect pollinator scientists. The conservation practitioners include representatives from UK industry (including retail), environmental non‐government organisations and nature conservation agencies. We collaboratively developed a long list of 246 knowledge needs relating to conservation of wild insect pollinators in the UK. We refined and selected the most important knowledge needs, through a three‐stage process of voting and scoring, including discussions of each need at a workshop. We present the top 35 knowledge needs as scored by conservation practitioners or scientists. We find general agreement in priorities identified by these two groups. The priority knowledge needs will structure ongoing work to make science accessible to practitioners, and help to guide future science policy and funding. Understanding the economic benefits of crop pollination, basic pollinator ecology and impacts of pesticides on wild pollinators emerge strongly as priorities, as well as a need to monitor floral resources in the landscape.